Issues in the Formation of Students' Ecological Values in the Process of Teaching Biology (Journal of Educational Sciences, 2025)
The article examines the hierarchy of ecological values and their transformation, as well as the relevance of universal human values in contemporary society. It emphasizes that fostering value development among students requires the integration of innovations into the educational process. Such innovations may be connected to meeting societal needs and promoting students' self-realization.Environmental education plays a decisive role in forming a system of ecological values that regulate the interaction between humans, the environment, and society. Fundamental ecological values, such as "life as the highest value," "nature as a universal value," "the value of health and a healthy lifestyle," and "the value of biodiversity," among others, are imparted to students in biology classes.The strategic directions of state policy aimed at ensuring sustainable development and improving science education underpin the development of methodological approaches to forming ecological values during biology instruction. The concept of global environmental education and the priorities of socio-economic, humanitarian, and scientific development of society are closely related to this process.Scientific and methodological research in biology education pays special attention to the formation of ecological culture, the development of an emotional and value-based attitude toward nature, the establishment of ecological guidelines, and the scientific and methodological justification of these processes.The article presents the results of a study on school teachers' opinions regarding the formation of ecological values in biology teaching. The survey included 79 teachers, who indicated that senior classes in general education schools face challenges in defining and fostering ecological principles.  Key words: value, ecological values, "man-society-biosphere", educational process.